Anesthetic experience of methemoglobinemia detected during general anesthesia for gastrectomy of advanced gastric cancer -A case report - Cho, Sam Soon; Park, Yong Duck; Noh, Jae Hoon; Kang, Kyoung Oh; Jun, Hee Jung; Yoon, Jin Sun (Korean journal of anesthesiology, 2010)
Methemoglobinemia is an uncommon but potentially fatal disorder. Most cases have no adverse clinical consequence and require no treatment, but methemoglobinemia is often overlooked as a cause of low oxygen saturation, and often mistaken for the more common causes of hypoxia by anesthesiologists despite simple bedside tests that indicate the presence of this treatable abnormality. We present a 68-year-old female patient who underwent gastrectomy for advanced gastric cancer with bleeding. In the preoperative period, the patient showed cyanosis and oxygen saturation was 85% by pulse oximeter, but oxygen saturation by arterial blood gas analysis was 100%. After tracheal intubation, the methemoglobin level was 18.3%. Ascorbic acid and methylene blue were administered. During preanesthetic evaluation, the patient had not informed the anesthesiologist that she had been taking dapsone.